Round the Red Lamp - Doyle, Arthur Conan (Saga Egmont, 2022)
First published in 1894, ‘Round the Red Lamp’ is a collection of mostly medical themed stories from the famous Sherlock Holmes author Sir Arthur Conan Doyle, no doubt drawing on his own experiences as a physician. Stories in the collection include the squeamish tale ‘His First Operation’, childbirth story ‘The Curse of Eve’ and a sweet, sentimental account about the passage of time in ‘Behind the Times’.